PENGARUH SUPERVISI TERHADAP DISIPLIN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI - Aris Eddy Sarwono, Warsono & (Universitas Slamet Riyadi, 2009)
Abstract The goal of this research is to analyze moderation effect of motivation on supervision influence against teacher work discipline of SMA Negeri I Karanganyar.This research located in SMA Negeri I Karanganyar. Population in this research is teachers of SMA Negeri I Karanganyar which is in amount of 78 peoples. Whereas the population is relative small, so this research is a census because the whole of the research are taken as sample. The space of the research is focused on supervision aspects and its influence against work discipline of the teachers with motivation as moderating. Based on the result of regression, it is gained that F value is 417,482. F value in this regression 2 decreased become 293,286. From the comparison of regression analysis experienced decreasing of F value in amount 124,196. This showed that moderation of motivation variable significant weakened supervision influence against work discipline. At the moment of supervision influence is strong, so motivation becomes weak, and on the contrary, if supervision influence is weak against work discipline, so motivation becomes strong. Keywords: supervision, work discipline, motivation.